Improving the Legitimacy of Proximity Mobile Payment: The Contributions of Neo-Institutional Theory - Abbes, Intissar; Hallem, Yousra; Hikkerova, Lubica; Chbak, Nouha (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2021)
This article explores the legitimacy of a proximity mobile payment (PMP) system by exploring the social aspects related to its use (social acceptability). A qualitative study was conducted with 27 customers using a PMP service and 8 professionals familiar with PMP. Results highlighted the importance of the consumption system and service provider as institutions. More specifically, a PMP system can only be accepted and legitimized if it is supported by the three institutional pillars: cognitive, normative and regulatory. Recommendations are thus proposed to PMP service providers in order to rethink and optimize the implementation of their PMP system.